The effect of the COD: N ratio on mainstream deammonification in an integrated fixed-film activated sludge sequencing batch reactor. (November 2020) - Azari, M.; Aslani, A.; Denecke, M.
Abstract: For eight months, a sequencing batch reactor (SBR) with integrated fixed-film activated sludge (IFAS) was operated in ambient temperature to study engineering and practical aspects of application of deammonification for mainstream conditions. For biofilm formation, K3 Kaldnes carriers were used, where the anaerobic ammonium oxidation (anammox) process can occur in deep layers of biofilm, while partial nitritation occurs in oxygen-rich outer layers. After the initial running phase of the reactor (Phase 1) to provide time for microorganisms to adapt, the COD: N ratio increased to around 2.6 in Phase 2 through reducing the ammonium concentration and increasing COD in synthetic wastewater to get closer to mainstream conditions. The total reaction time in each half-day batch cycle was kept 625 min throughout various phases, but the duration of intermittent aeration was regulated at 4 ± 1 min. While final nitrogen removal efficiency (NRE) for Phase 1 was 43%, at the end of Phase 2, it decreased to 37%. However, a maximum NRE at 90% was achieved during Phase 2. The identification of the responsible microorganisms was made through Fluorescence in situ hybridization (FISH), while Mixed Liquor Suspended Solid (MLSS) and Mixed Liquor Volatile Suspended Solid (MLVSS) was used to estimate the physical presence of bacteria. Ammonium oxidizing bacteria (AOB) and anaerobic ammonia-oxidizing bacteria (AnAOB) were dominant bacteria, respectively. The adverse effects of a gradual increase of COD: N ratio from 0.17 to more than 2.0 caused a decline in NRE to around 15%. Highlights: Increase of COD: N ratio to around 3 led to an unstable ammonium degradation. Higher COD: N in mainstream deammonification can reduce the efficiency by 15%. Decreasing COD and increasing ammonium lead to improve NRE from 31% to 46%. FISH proved the presence of anammox bacteria in the reactor, but more in liquor.